White Pathology: The African American Critique of Black Pathology Discourse at the Turn of the Century - Davis, Matthew (My University, 2018)
This project examines the ways African American authors from the turn of the twentieth century challenged racist violence and white supremacy and sought to create nuanced political responses and strategies. I focus on how Pauline Hopkins, Sutton Griggs, and Charles Chesnutt respond to a discourse of black pathology, exemplified in the work of Thomas Dixon, that inscribes racial difference in both biological and cultural terms. This discourse of black pathology emboldens white racism and enables violence against African Americans, so these critical voices identify and subvert that discourse to paint white supremacy in pathological terms.
Keywords: Black Pathology Discourse; African American Literature; Nineteenth Century; Twentieth Century